Para-aortic nodal metastases in cervical cancer: a blind spot in the International Federation of Gynecology and Obstetrics staging system: current diagnosis and management. (January 2015) - Hwang, Lindsay; Bailey, April; Lea, Jayanthi; Albuquerque, Kevin
ABSTRACT : In cervical cancer, para-aortic nodal (PALN) metastases at presentation is a strong indicator of poor prognosis. Despite this, International Federation of Gynecology and Obstetrics staging system does not require evaluation of lymph node involvement and does not incorporate clinically detected PALN into the staging system. In the USA, despite screening, a significant number of women still present at an advanced stage often with nodal metastases. While the presence of PALN metastases often indicates occult systemic disease, it is possible with modern therapies to provide long-term control of disease in a percentage of patients. We review the epidemiology, diagnosis and treatment of PALN metastases in cervical cancer outlining advances in modern imaging and combined modality therapies (surgery, chemotherapy and radiation therapy).